US Print Culture, Literary Narrative, and Slow Reading in the Age of Big Data: Steve Tomasula’s VAS – An Opera in Flatland - Kley, Antje (Medium, Object, Metaphor: The Printed Book in Contemporary American Culture, 2019)
Antje Kley considers how contemporary fiction in the medium of the printed book may offer its readers a critical perspective on the politics of statistical data acquisition, specifically in the domains of personal quantification and self-optimization. She reads Steve Tomasula’s formal experiments with typeface, page layout, and other elements of book design in his multimodal novel VAS as a literary intervention into a culture whose decision-making processes increasingly rely on probabilistic predictions based on statistical data analytics rather than on ethical deliberation. Kley locates the subversive potential of literature in its ability to subjectify and sensorially refract knowledge production and communication, offering its readers conceptual alternatives to the detached abstracting perspective often privileged in scientific knowledge cultures, here represented by biomedicine.<br
CRIS-Team WoS Importer:2020-10-02